A weird and wild beauty : the story of Yellowstone, the world's first national park - Peabody, Erin (Sky Pony Press, 2016)
Examines the expedition of 1871 that led to the passing of the Yellowstone Park Bill, making Yellowstone the first national park and paving the way for future preservation of national habitat. Includes maps and color photographs.